The attenuation of correlation coefficients: a statistical literacy issue. (15th September 2015) - Trafimow, David
Summary: Much of the science reported in the media depends on correlation coefficients. But the size of correlation coefficients depends, in part, on the reliability with which the correlated variables are measured. Understanding this is a statistical literacy issue.